Optimization of the basin and inlet channel of a gravitational water vortex hydraulic turbine using the response surface methodology. (March 2022) - Velásquez, Laura; Posada, Alejandro; Chica, Edwin
Abstract: The gravitational water vortex hydraulic turbine is an appropriate turbine to be used under from a small to medium water flow rate and at a low head. This turbine extracts energy from an induced vortex in a basin, using a coaxial rotor with a vertical axis. The gravitational turbine has efficiencies that vary between 17 and 85%. Increasing the circulation was required in order to achieve the highest efficiency. The circulation is a function of some geometric parameters of the turbine, such as the ratios between the basin diameter ( D ) and the outlet diameter ( d ), d / D ; the basin height ( H ) and D, H / D ; the inlet channel width ( w ) and D, w / D ; the inlet channel height ( h ) and D, h / D ; the inlet channel long ( L ) and D, L / D ; and the wrap-around angle ( γ ). Response surface methodology was utilized to determine the optimal geometry that results in the highest circulation. The values of the six variables that give the highest circulation of 2.089 m 2 /s were d / D  = 0.167, H / D  = 1.840, w / D  = 0.2, h / D  = 0.599, L / D  = 0.500 and γ  = 179.976°. In addition, an exponential equation was proposed for calculating the inlet velocity for each treatment. This equation is a function of d / D and the coefficient of discharge, C d . The results of the exponential function were compared with experimental data from other investigations. Graphical abstract: Image 1 Highlights: GWVHT is a turbine suitable to use in low head and small to medium water flow rates. GWVHT is optimized through the response surface methodology. Transition-state, VoF, and k- ε RNG model were chosen to perform the CFD analyses. The highest circulation obtained was 2.089 m 2 /s.